Functional Genetic Variant in ATG5 Gene Promoter in Acute Myocardial Infarction - Yexin Zhang; Xiaohui He; Jiarui Li; Wentao Yang; Yinghua Cui; Shuchao Pang; Haihua Wang; Bo Yan (Cardiology Research and Practice)
Coronary artery disease (CAD) including acute myocardial infarction (AMI) is an inflammatory and metabolic disease mainly caused by atherosclerosis. Dysfunctional autophagy has been associated with abnormal lipid metabolism and inflammation. In previous studies, we have reported altered autophagic activity in AMI patients. As autophagy-related protein 5 (ATG5) is a core protein in autophagy, we speculated that altered ATG5 level may contribute to CAD and AMI development. In this study, the promoter of the ATG5 gene was genetically and functionally investigated in large groups of AMI patients (n = 378) and ethnic-matched healthy controls (n = 386). The results showed that a total of 15 genetic variants including 6 single-nucleotide polymorphisms (SNPs) in the ATG5 gene promoter were found in this study population. A novel deletion variant (g.106326168_70delTCT) and an SNP [g.106325757C > G (rs190825454)] were found in one 66-year-old male patient with non-ST-segment elevated AMI, but in none of controls. In cultured HEK-293 and H9c2 cells, the deletion variant significantly decreased the transcriptional activity of the ATG5 gene promoter (P<0.01). In contrast, the genetic variants either identified only in controls or found in both AMI patients and controls did not affect the transcriptional activity of the ATG5 gene promoter (P>0.05). Furthermore, an electrophoretic mobility shift assay showed that the deletion variant evidently affected the binding of a transcription factor. Therefore, the genetic variant identified in AMI may affect the activity of the ATG5 gene promoter and change the ATG5 level, contributing to AMI as a rare risk factor.